Understanding consumer perceptions of hotel toiletries - Payne, Jessie Elizabeth (Kansas State University, 2021)
A hotel staple across the world is providing toiletries in guest’s bathrooms. It is a common expectation from consumers to find complementary bath items during the duration of their stay. However, there is no research known that explores which specific features of these toiletries are preferred by hotel guests. Combining hotel industry and sensory research techniques will allow this thesis to gain a full profile of the different hotel toiletries along with consumer expectations, preferences, and usage of these products. The objectives of this research are to a) identify key features of hotel toiletries (specifically hotel shampoos and lotions) that maximize consumer acceptance, b) determine how variables, such as hotel price point (luxury vs. economy), affect consumer preferences for toiletries features, and c) determine the "ideal" model of hotel shampoos and lotions. First, 22 frequent hotel guests and hotel toiletry users participated in four different focus group sessions. These sessions were divided based on the type of hotel toiletry the consumers used (i.e., lotion or shampoo) and the type of hotel the participant most regularly used (i.e., economy or luxury). The results showed that perceived differences were apparent between the economy and luxury hotel guests. The economy guests claimed that brand name and ingredients listed on the hotel toiletry were of high priority, while luxury hotel guests were not concerned with these characteristics. Luxury hotel guests were concerned with the initial appearance and display of the hotel toiletry products such as product color and packaging ‘uniqueness’. Though this was true, these two types of hotel guests were shown as both groups wanted relaxing ‘spa’ like scents for shampoos and thick/creamy textures for lotions. In the second study, a group of trained panelists was used to generate sensory characteristics of 33 shampoos and 30 lotions, to validate and determine any additional attributes to describe hotel shampoos and lotions. This study concluded in six additional attributes being added to the list created during the focus group sessions. Two attributes were added for hotel shampoos, while four more attributes were included for hotel lotions. From this research a consumer-friendly attribute list was created to use in the final study of this thesis. This attribute list included 30 total features for hotel shampoos and 34 total features for hotel lotions. The second part of this study included a sorting task with trained and naïve consumers to determine the similarities and differences between hotel shampoos and lotions. There were various differences such as aroma strength, and also similarities such as thick texture. In the final study, two Maximum Difference (Max-Diff) surveys (one for hotel shampoos and one for hotel lotions) were conducted. A total of 312 participants were recruited to determine the most and least important features of hotel toiletries. It was determined that in order to maximize consumer acceptance, specific packaging and sensory features should be used for hotel shampoos and lotions. For example, hotel shampoos should have the ability to lather and have a relaxing, spa-like scent. For hotel lotions, a non-greasy, moisturizing, and smooth feel on skin should be present. This research will help the hotel industry identify the key features of hotel shampoos and lotions, how these features influence consumer acceptance, and the potential modifications that should be made in the product category. This thesis also explores the use of various sensory and consumer research techniques that could help identify and prioritize product features to maximize consumer acceptance of various product categories.
Keywords: Hotel; Shampoos; Lotions; Consumer; Toiletries; Features